UPAYA PONDOK PESANTREN DALAM MEMBENTUK KARAKTER DISIPLIN SANTRI DI PONDOK PESANTREN PUTRI AL MA’RUF KOTA KEDIRI - A'yun, Nayla Qurroti; Masrukin, Ahmad (Jurnal Pendidikan Islam, 2023)
This research aims to describe the efforts made by Islamic boarding schools to shape the disciplined character of students at the Al-Ma'ruf Islamic Boarding School, Kediri. The method used in this research is descriptive qualitative. Data collection techniques using interviews, observation and document study. Interviews were conducted with caregivers, teacher council, boarding school administrators, alumni and santri. With this interview the researcher obtained the data and information needed. Data analysis was carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of the research show that the discipline of Al-Ma'ruf students has been going well in terms of the activities that all students participate in and the time allocation for all activities as well as responsibility for the mandate given. This is proven by the researcher's analysis of the participation of students who arrived on time when participating in activities and carrying out the tasks they were carrying out. It is hoped that the data from this research can provide inspiration to Islamic boarding schools to maintain and improve the discipline of students because the key to success is discipline and trust.